Derivatives of 3-Hydroxypyridine in The Correction of Disorders in The Structural and Functional Properties of Erythrocytes in Experimental Acute Destructive Pancreatitis Due to Chronic Ethanol Intoxication: Pharmaceutical Science-Chemistry - .S. Litvinova, E; .V. Kharchenko, A; .S. Razinkova, N; .A. Ragulina, V (International Journal of Life Science and Pharma Research, 2022)
At present, acute pancreatitis only in some areas is a rather well-studied disease of the abdominal organs, however, the destructive forms of this disease have various developmental patterns, complications and, often unfavorable outcomes. The aim of the research is to establish the possibilities to correct the disorders in the functional and structural features of erythrocytes by 3-hydroxypyridine derivatives in experimental acute destructive pancreatitis due to chronic ethanol intoxication. In experimental acute destructive pancreatitis due to a 60-day ethanol intoxication there was a decrease in the content of proteins (a - ? ß -spectrin, ankyrin, anion transport protein, actin, gyceraldehyde-3-phosphate dehydrogenase, glutation-S transferase) and lipids (phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine, phosphatidylinositol, glycerophospholipids, sphingomyelin, phospholipids, triacylglycerol, sum of mono- and diacylglycerol), an elevated level of band 4.1 and 4.5 proteins, pallidin, dematin, tropomyosin and lipids (lysophosphatidylcholine, cholesterol, it’s esters, non-esterified fatty acids), a disorder in intrinsic cellular metabolism of erythrocytes (an increased concentration of lipid peroxidation products, a decreased activity of catalase, superoxide dismutase, degree of stable metabolites of nitrogen oxide and sorption indicators of membrane) in the erythrocyte membrane. The study has revealed that the greatest efficiency in correction of disorders in the functional and structural feutures of erythrocytes from among the derivatives of 3-hydroxypyridine has a compound ß - hydroxynicotinoylhydrazon 2-methyl-3-hydroxy-4-formyl-5-oxymethylpyrydine dihydrochloride, and the least one - 2-ethyl-6- methyl-3-hydroxypyrydine malate (etoxydol), the administration of 2-ethyl-6-methyl-3-hydroxypyrydine succinate (mexidol) has shown an intermediate result.